Pendampingan Guru Dalam Penyusunan Proposal dan Laporan Penelitian Tindakan Kelas dan Peningkatan Kemampuan Literasi dan Numerasi Siswa Melalui Program Lopo Pintar di SDK Muder Teresa Kupang - Tokan, Moses Kopong; Imakulata, Mbing Maria; Bani, Marsi D. S. (Jurnal Kelimutu Pengabdian Masyarakat, 2024)
In general, teachers at Murder Teresa Catholic Primary Schools and Catholic Junior High Schools have not conducted Classroom Action Research, therefore this activity is very important to carry out to help teachers. This activity aims to help teachers understand CAR, write CAR proposals, create CAR reports, and write published articles as well as help students who experience learning difficulties. The stages of this activity are a presentation of material, practice, and assistance with writing, as well as mentoring students during 4 meetings. The results of the activity show that there has been an increase in knowledge about CAR and the publication of scientific papers and students have experienced an increase in literacy and numeracy